Monitoring of soil transmitted helminth (STH) Helminthiasis on school-age children in final garbage dump, Bantar Gebang, East Bekasi - Reza Anindita; Maulin Inggraini (Department of Biology, Faculty of Sci and Tech, Universitas Islam Negeri Alauddin Makassar, 2023)
The prevalence of helminthiasis in West Java is 13.9%, but there is no data on STH helminthiasis on school-age children in the final garbage dump (FGD), Bantar Gebang, East Bekasi, Indonesia. Therefore, it is necessary to monitor STH helminthiasis on school-age children living around FGD. This study aims to determine the description of helminthiasis on school-age children who live in the FGD Bantar Gebang, Indonesia. This type of research is descriptive quantitative with a cross-sectional design. The sample in this study consisted of 79 stool children aged 5-9 years, 5 g of fly vectors from wet, dry, and soil were taken from 36 locations around the FGD. STH examination on stool, flies, and soil samples was carried out using the native, Harada Mori, flotation, and sedimentation methods. All data were analyzed using a descriptive approach to determine the percentage of the incidence of STH. The results of this study, among others, from 79 children there were six (7.60%) children infected with STH with the genus or species Ascaris lumbricoides, hookworm, and Trichuris trichiura. As for the 18 points of soil extraction, there were 12 (66.7%) positive points containing hookworm larvae, while the flies found were more dominant in Musca domestica than Chrysomya sp. with worm parasites attached to the fly's body are Ascaris lumbricoides, Diphyllobothrium latum. Enterobius vermicularis, hookworm, Hymenolepis sp., Schistosoma sp., Trichuris trichiura. The conclusion of this study is percentage incidence of STH helminthiasis on school-age children living in FGD Bantar Gebang is 7.60% which is in the low category.